ECONOMICAL EDUCATION OF UKRAINE: UNIQUE COMBINATION OF TECHNOLOGICAL AND CLASSICAL UNIVERSITIES - Герасимова, Е. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Changes of basic paradigms of perception of the world, which are first of all connected with processes of globalization in economical branch caused the appearance of princely new conception of economical-thrifty knowledge which activated the process of reformation of fundamental type of economical education in universities.